The EU’s Precarious Old Normal and the Need for Reform - Hubert Gabrisch (Wirtschaftsdienst)
Abstract The EU has been in crisis mode since 2008. The old normality is the big political goal, but a return to the status quo ante is not really desirable. Unfortunately, European politics has no concept for the future of the Union after the COVID-19 pandemic. This could prove to be an existential problem for the Union in its current form. The article analyses the inner context of the various crises since 2008, points out possibilities for reforming the Union’s architecture in the central fields of fiscal and monetary policy and warns against further crises and the marginalisation of the Union on a global scale.